Effect of Additives on Preparation of Chlorine Scavenger Powder - Gao, Xiaorong; Cui, Longhui; Li, Xing; Shen, Jun; Wei, Wenlong; Chang, Honghong; Kou, Ziming (Asian Journal of Chemistry, 2015)
Calcium hydroxide as the principal component was prepared for chlorine scavenger powder by wet process. The influences of different species and amount of silicone oil and surfactants on surface modification of calcium hydroxide were investigated, by using sieve ratio, bulk density, contact angle and SEM. The experimental results indicated that surface modification effect of calcium hydroxide modified by sodium stearate was better than that of sodium dodecyl benzene sulfonate and the suitable dosage was 2 % and that calcium hydroxide powders with the addition of amino silicone oil, emulsifying silicon oil and water-based silicone oil had good modification effect. Considering the operational requirement of powder fire extinguisher, or large bulk density, amino silicone oil and emulsified silicon oil were satisfied the priority selection which the suitable dosage was 3 %. On the basis of above modification, sodium silicate was also used as composite modifier. The results showed that the powders adding 2 % of sodium silicate had ideal dispensability and anti-caking ability that 1 g of calcium hydroxide modified by sodium stearate, emulsified silicon oil and sodium silicate could be absorbed 0.297 g chlorine.